Perioperative Blood Pressure Control in Carotid Artery Stenosis Patients With Carotid Angioplasty Stenting: A Retrospective Analysis of 173 Cases - Zheng, Longlong; Li, Jiang; Liu, Haixiao; Guo, Hao; Zhao, Lei; Bai, Hao; Yan, Zhongjun; Qu, Yan (Frontiers in Neurology, 2020)
Background: Carotid angioplasty stenting (CAS) is a currently widely used surgical treatment of carotid artery stenosis. However, the influences of the perioperative blood pressure (BP) on patients’ prognosis remain unclear. Objective: The present study was designed to explore the effects of different perioperative BP control strategies on CAS patients’ prognosis. Methods: 173 consecutive patients admitted between January 2016 and April 2019 were reviewed retrospectively. The outcomes of patients with different systolic BP (<120 mmHg, 120–130 mmHg, >130 mmHg) before CAS and within 24 h after CAS were compared. The primary outcomes were the incidence of secondary cerebral infarction (CI) and intracranial hemorrhage (ICH) after CAS. The secondary outcome was the incidence of unfavorable discharge and in-hospital death. The unfavorable discharge was defined as modified Rankin Scale (mRS) score 3-5 at discharge. Results: There was no significant difference between the incidences of ICH (P=0.803) and CI (P=0.410) in patients with different BP before CAS. The patients with post-CAS BP values of >130 mmHg had a 37.67-fold increased risk (95% CI: 6.79-209.01) of ICH comparing with others. While no significant difference was observed on the incidence of CI (P=0.174) among the patients with different post-CAS BP values. The patients with post-CAS BP values of >130mmHg also had a significantly higher incidence of unfavorable discharge (P=0.002) and in-hospital death (P=0.001) comparing with others. Conclusion: High BP (>130 mmHg) within 24 h after CAS significantly increases the risks of secondary cerebral hemorrhage, unfavorable discharge, and in-hospital death. Thus, the BP should be controlled below 130mmHg in the first 24 h after CAS.